Pengaruh Work-Family Conflict dan Stres Kerja terhadap Kepuasan Kerja Perawat Wanita yang Sudah Menikah di Rumah Sakit Panti Rini Yogyakarta - Manurung, Yohana Putri Jihan; Pramudita, Dismas Persada Dewangga (Universitas Syiah Kuala, 2025)
Human resources are one of the most crucial aspects in ensuring the sustainability of an organization. Therefore, both physical and mental health must be given proper attention. On the other hand, nurses, who are expected to consistently maintain good social conditions, especially when dealing with certain situations, often become vulnerable to stress and fatigue. In addition to work-related pressures, married female nurses also experience additional strain due to the double roles they must fulfill as both mothers and workers. Hence, this study aims to examine the effect of work-family conflict and job stress on job satisfaction among married nurses at Panti Rini Hospital Yogyakarta. Data collection was carried out through the distribution of physical questionnaires. The collected data were processed using SPSS version 29, with validity and reliability tests employed to assess the instruments, while descriptive analysis and multiple linear regression were used as data analysis methods. The results of this study indicate a significant negative effect of work-family conflict and job stress on job satisfaction.